2005
DOI: 10.1002/bem.20145
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic pathway of magnetized fluid‐induced relaxation effects on heart muscle

Abstract: The effect of magnetized physiological solution (MPS) on isolated, perfused snail heart muscle contractility, (45)Ca uptake and intracellular level of cAMP, and cGMP was studied. The existence of the relaxing effect of MPS on heart muscle at room temperature (22 degrees C) and its absence in cold medium (4 degrees C) was shown. The MPS had a depressing effect on (45)Ca uptake by muscles and intracellular cAMP content and an elevating effect on intracellular cGMP level. It is suggested that the relaxing effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…metabolism has a crucial role (Adey 1993;Blackman et al 1985Blackman et al , 1988. It was also shown that SMF had elevation effect on intracellular cyclic guanosine monophosphate (cGMP) (Ayrapetyan et al 1994(Ayrapetyan et al , 2005, which leads to the activation of Na ? /Ca 2?…”
Section: Introductionmentioning
confidence: 97%
“…metabolism has a crucial role (Adey 1993;Blackman et al 1985Blackman et al , 1988. It was also shown that SMF had elevation effect on intracellular cyclic guanosine monophosphate (cGMP) (Ayrapetyan et al 1994(Ayrapetyan et al , 2005, which leads to the activation of Na ? /Ca 2?…”
Section: Introductionmentioning
confidence: 97%
“…Then, the question was raised-Which is the reason for the IR-induced increase in the number of a 3 ouabain receptors as compared to non-radiated cells? In previous study was shown that ouabain at high and low concentrations, leads to the increase in cAMP-dependent membrane phosphorylation causing a decrease in the membrane receptors affinity to ligand (Arvanov et al 1992;Ayrapetyan et al 2005) and the activation of Na ? /Ca 2?…”
Section: Resultsmentioning
confidence: 98%
“…The up and down movements of the baseline of records showed the heart contraction and relaxation, respectively. The setup for the registration of heart muscle contractility was schematically represented and described in detail in Ayrapetyan et al [2005], Figure 1. 45 Ca uptake by muscles incubated in normal and H 2 O 2 -containing PS was measured by 45 Ca isotope having specific activity: 0.185-1.85 GBq/mg Ca, 5-50 mCi/mg Ca (production of Amersham Life Science, Inc., Arlington, TX).…”
Section: Methodsmentioning
confidence: 99%